2005
DOI: 10.1016/j.ymthe.2004.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and local biological effects of an intratumoral injection of mda-7 (IL24; INGN 241) in patients with advanced carcinoma: a phase I study

Abstract: The melanoma differentiation-associated gene-7 (mda-7; approved gene symbol IL24) is a tumor suppressor gene whose expression induces selective apoptosis in tumor cells. To characterize the safety and biologic activity of mda-7 gene transfer, we conducted a phase I trial using intratumoral injections of an adenovirus containing the mda-7 construct (Ad-mda7; INGN 241; 2 x 10(10) to 2 x 10(12) vp) in 28 patients with resectable solid tumors. One hundred percent of injected lesions demonstrated INGN 241 vector tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
194
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 24 publications
3
194
0
1
Order By: Relevance
“…A phase I trial using intratumoral injections of Ad-IL-24 (INGN 241) was conducted in patients with refractory cancer. [14][15][16] As expected, INGN 241 can induce apoptosis in a large percentage of tumor volume via a single intratumoral injection. However, as the INGN 241 virus is nonreplicating, the clinically significant response can be seen only with repeat injection of INGN 241.…”
Section: Introductionmentioning
confidence: 56%
“…A phase I trial using intratumoral injections of Ad-IL-24 (INGN 241) was conducted in patients with refractory cancer. [14][15][16] As expected, INGN 241 can induce apoptosis in a large percentage of tumor volume via a single intratumoral injection. However, as the INGN 241 virus is nonreplicating, the clinically significant response can be seen only with repeat injection of INGN 241.…”
Section: Introductionmentioning
confidence: 56%
“…mda-7 (INGN 241) was very encouraging, indicating that multiple intratumoral injections could elicit an objective clinical response with complete tumor regression in one melanoma patient. 13,16,18,[27][28][29] Of added significance, all of the patients in the clinical trial had already received several rounds of prior therapy (chemotherapy and/or radiation therapy) and the efficacy of Ad.mda-7 in these patients strongly suggests that administration of Ad.mda-7 in patients with early stage cancer might provoke an even more pronounced therapeutic response. These findings firmly establish mda-7/IL-24 as a bona fide candidate suppressor gene with potential to provide an effective alternative to conventional cancer treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] A momentous step in the evolution of mda-7/IL-24 as a potential therapeutic gene was the evaluation of Ad.mda-7 (INGN 241) in a phase-I clinical trial by intratumoral injection in patients with advanced solid tumors, including melanomas. 13,16,18,[27][28][29] These studies indicated that mda-7/IL-24 was safe and could induce as much as 70% apoptosis in tumors following a single injection of recombinant virus, and with multiple injections, it promoted objective clinical responses, especially in melanoma patients. 13,16,18,[27][28][29] This exciting transition from the 'laboratory to the clinic' provides direct support for using mda-7/IL-24 to develop an effective gene-based therapy for cancer, including metastatic melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17] Forced expression of mda-7/IL-24, using Ad.5 (Ad.5-mda-7), inhibits growth and kills a broad spectrum of established cancer cell lines in vitro, without exerting injurious effects in multiple types of normal human epithelial cells, fibroblasts, melanocytes or astrocytes. [16][17][18][19][20][21] Considering its robust cancer-specific apoptosis-inducing ability (by inducing endoplasmic reticulum stress) and tumor growth-suppressing properties in nude mice human tumor xenograft models, Ad.mda-7 (INGN 241) was evaluated in a phase I clinical trial in patients with advanced cancers. The results obtained from this trial demonstrate both safety and clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%